ANALISA PERENCANAAN ARUS KAS TERHADAP PENGENDALIAN INTERN PADA KOPERASI KOPDIT RUKUN PALEMBANG - Maulan irwadi; Masagus Adriansya Putra; Emilia Gustini (Universitas Indo Global Mandiri)
The purpose of this study was to determine how the process of preparing a cash budget, analysis of the factors causing the variance between budget and actual cash budget and budget planning and control of cash in the Cooperation Kopdit Rukun Palembang with the observation period the cash budget in 2013 and 2014.In this study, researchers used a qualitative analysis method and analysis kuantiatatif. Where analyzes were performed using the data in the amount set forth to explain an explanation of the figures later described back in the form of prose description language or standard language.The results showed that: (1) In the process of preparing a cash budget on Cooperation Kopdit Rukun of Palembang using a bottom-up approach to budgeting that is where the budget is prepared and put up by the parties to implement the budget. (2) The cause of the difference (variance) between budget and actual cash budget is a cooperative internal and external factors. (3) the cash budget planning by estimating finance and analysis of the activities, both routine and non-routine activities. (4) Control of the cash budget on Cooperation Kopdit Rukun of Palembang form of control on a cash budget a good budget deviation was farvorable or unfarvorable and to anticipate as well as revisions to the deviations that occur. Keywords: Cash Budget, Planning, Controlling